Respuesta :
Answer:
Option (2) and (5) is correct.
x = -5 and x = 3
Step-by-step explanation:
Given : equation (x + 5)(x – 3) = 0
We have to find the solution of the given equation (x + 5)(x – 3) = 0 and choose the correct option from the given options.
Consider the given equation (x + 5)(x – 3) = 0
Using zero product rule, [tex]a\cdot b=0 \Rightarrow a=0\ or\ b=0[/tex]
Thus,
(x + 5) = 0 or (x – 3) = 0
Simplify for x, we have
x = -5 and x= 3
Thus, Option (2) and (5) is correct.
The values of x are -5 and 3
Zero of an equation
Given the expression (x + 5)(x – 3) = 0
This is already the factored form of aquadraric equation
Equating each factors to zero, we will have:
x+5 = 0
Subtract 5 from both sides
x+5-5 = 0-5
x = -5
Similarly, x - 3 = 0
x-3+3 = 0+3
x = 3
Hence the values of x are -5 and 3
Learn more on zeros of equation here: https://brainly.com/question/17145398